CAT III - longitudinal autolanding LQR design - Marcos Vinícius Campos (2006)
Automatic landings have been performed routinely for many years. However the design of flare and landing control systems with a suitable performance and a high level of reliability remains a very difficult task. In the present scenario, the increasing in the landing capacity of airports is mandatory by limiting the time each aircraft occupies the runway. To limit the occupancy time, the reduction of touchdown zone is essential since landings too close of the exit could result in a missed exit and therefore in a decreasing of landing rate. Give this context, the present work aims to propose an autoland flare law development for a 50 seat regional jet using Linear Quadratic Regulator technique. An accurate flare path, good rejection to turbulence, simplicity in implementation and, moreover, improved longitudinal touchdown dispersion are some of desirable features of design. In development of autoland control system, full feedback was used as control law configuration. Simulations were performed with non-linear model of the aircraft based on the equations of rigid body movement. The gains of LQR flare law were obtained though global optimization using Genetic Algorithms. The robustness of resulting close-loop system was tested with respect to ground-effect, wind shear and out-of-trim conditions. The performance of LQR flare law was compared with Model-Following design. Steady wind and turbulence models were used as disturbances for stochastic evaluation of the methods. The explicit flare trajectory defined in space, not in time, resulted on the improved touch down dispersion achieved by LQR design.